Hypermobility Spectrum Disorders and Sport Participation: When Movement Helps and When It Harms – a Narrative Review of the Medical Evidence - Kwiatkowska, Maja; Palian, Jakub; Huzarska, Karolina; Kurzyński, Szymon; Baraniecka, Aleksandra (Quality in Sport, 2026)
Background: Joint hypermobility (JH), the hypermobility spectrum disorders (HSD) and hypermobile Ehlers–Danlos syndrome (hEDS) are common, under-recognised connective-tissue phenotypes in which the same ligamentous laxity that may favour performance in aesthetic disciplines can also predispose to injury, chronic pain and deconditioning. Aim: To critically synthesise the current medical evidence on how sport and structured exercise can both harm and help hypermobile individuals, and to derive practical, risk-stratified implications for athletes, clinicians and physiotherapists. Material and methods: Narrative review of systematic reviews, meta-analyses, prospective cohorts, case–control studies and intervention trials addressing JH, HSD and hEDS in the context of sport, injury and rehabilitation. Results: The Beighton score remains the standard screen but is an imperfect, upper-limb-weighted measure of generalised JH. Meta-analyses indicate that generalised JH increases knee/anterior cruciate ligament and shoulder injury risk, especially in contact sport, whereas ankle risk is largely unchanged; several prospective cohorts in football, soccer and dance found no overall excess of injury. Symptomatic, not asymptomatic, hypermobility drives adverse outcomes. Conversely, individualised proprioceptive, stabilisation and even supervised heavy-resistance programmes reduce pain and kinesiophobia and improve function and quality of life, whereas inactivity perpetuates a self-reinforcing symptom cycle. Conclusions: Movement is therapeutic when graded, supervised and symptom-guided, yet potentially harmful when laxity is symptomatic or syndromic. Management should be individualised, multidisciplinary and stratified by symptom burden and EDS subtype, with vascular EDS representing an extreme high-risk exception.